Effects of Increasing Soybean Meal in Diets with or without Distillers Dried Grains with Solubles on Growth Performance and Carcass Characteristics of Pigs in Early and Late Finishing Phases - Paula Giacomini; Katelyn N. Gaffield; Robert D. Goodband; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Amy Petry; Margaret Putnam; Aaron Gaines; R. Dean Boyd; Caleb Shull; et al. (Kansas Agricultural Experiment Station Research Reports, 2025)
This study aimed to determine the minimum soybean meal (SBM) inclusion in diets with or without distillers dried grains with solubles (DDGS) to optimize growth performance and carcass characteristics in finishing pigs. For the early finishing period (Exp. 1), a total of 4,080 pigs were used in a 28-day trial. Dietary treatments were arranged in a 2 × 4 factorial with main effects of DDGS (none or 30%) and increasing SBM (low, low-medium, medium-high, and high). There were 34 pigs per pen and 15 pens per treatment. Diets without DDGS contained 17.5, 23.3, 29.1, or 34.9% SBM, while diets with DDGS contained 3.9, 12.8, 21.8, or 30.6% SBM. For the late finishing period (Exp. 2), a total of 3,984 pigs were used in a 28-day trial. Diets were also arranged in a 2 × 4 arrangement with main effects of DDGS (none or 15%) and SBM (low, low-medium, medium-high and high). There were 30 to 34 pigs per pen and 15 pens per treatment. Diets without DDGS contained 6.5, 11.5, 16.4, or 21.3% SBM while diets with DDGS contained none, 6.4, 12.8, or 19.2% SBM. The NE of corn was assumed to be 1,228 Kcal/lb and soybean meal was assumed to be 1,267 Kcal/lb (103% of corn NE). Following the 28-day growth study, pigs were marketed on a fixed weight basis across three marketing events, and carcass characteristics were collected. Between experiments, from 140 to 175 lb, pigs were fed a common diet with 7.5% DDGS. In Exp. 1, a tendency (P = 0.088) for a linear interaction between DDGS and SBM level was observed for ADG, where increasing SBM decreased ADG in diets with 30% DDGS but did not affect diets without DDGS. Pigs fed 30% DDGS had decreased (P ≤ 0.01) ADFI and poorer F/G than pigs fed the corn-SBM-based diet without DDGS. Increasing SBM, regardless of DDGS inclusion, decreased ADFI (linear, P = 0.001) and improved F/G (linear, P = 0.043). In Exp. 2, from d 0 to d 28, an interaction (linear, P ≤ 0.05) between DDGS and SBM level was observed for ADG and ADFI, where increasing SBM reduced ADG and ADFI only in diets containing 15% DDGS. Pigs fed diets without DDGS had a tendency (P = 0.094) for improved F/G compared to pigs fed 15% DDGS. Increasing SBM improved F/G (linear, P < 0.001) but did not affect final BW. Marginal interactions between DDGS and SBM for percentage lean and loin depth (P ≤ 0.10) were observed with increasing SBM improving these traits to a greater extent in diets with 15% DDGS. Pigs fed diets without DDGS had increased (P < 0.05) HCW, carcass yield, and backfat depth. Increasing SBM decreased carcass yield (linear, P < 0.001) and backfat depth (quadratic, P = 0.033), regardless of DDGS inclusion. In conclusion, 30% and 15% DDGS negatively affected ADG and F/G in the early and late finishing periods, respectively. Feeding 29.1% SBM without DDGS and 21.8% SBM with 30% DDGS in the early period improved F/G without compromising ADG, while feeding 16.4% SBM without DDGS and 19.2% SBM with 15% DDGS in the late period improved F/G and carcass characteristics. Caloric efficiency was not changed with increasing SBM, suggesting that our initial estimate for SBM of 103% of the NE value for corn was appropriate.
Keywords: Distillers dried grains with solubles; finishing pig; soybean meal; swine